2013
DOI: 10.1016/j.jconrel.2013.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Localization of exogenous DNA to mitochondria in skeletal muscle following hydrodynamic limb vein injection

Abstract: ABSTRACT.Mitochondrial genetic disorders are a major cause of mitochondrial diseases. It is therefore likely that mitochondrial gene therapy will be useful for the treatment of such diseases. Here, we report on the possibility of mitochondrial gene delivery in skeletal muscle using hydrodynamic limb vein (HLV) injection. The HLV injection procedure, a useful method for transgene expression in skeletal muscle, involves the rapid injection of a large volume of naked plasmid DNA (pDNA) into the distal vein of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 42 publications
6
45
0
Order By: Relevance
“…At 2 min after the injection, the tourniquet was released. A schematic diagram of this methodology, which was previously reported for the HLV injection of naked pDNA [5], is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…At 2 min after the injection, the tourniquet was released. A schematic diagram of this methodology, which was previously reported for the HLV injection of naked pDNA [5], is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…pDNA was condensed with a polycation (Protamine) and the condensed pDNA was intravenously injected into the dorsalis pedis vein via HLV injection, which is similar to a previously reported method [5]. It is generally thought that the condensed pDNA is internalized into cells via hydrodynamic force, and mitochondrial localization of pDNA may be achieved.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the advantages of gene delivery therapy, recent advances in gene delivery, including plasmid DNA (pDNA), have been relatively restricted compared to the delivery of artificially synthesized oligonucleotides, including small interfering RNA (siRNA), anti-sense oligonucleotides and antimicro RNA oligonucleotides because of difficulty associated with developing a safe, effective non-viral vector for pDNA. 1) Hydrodynamic tail vein (HTV) injection is an established method for the successful gene delivery to hepatocytes, 2) myocytes, 3) mitochondria of limb muscles 4) and so on. Jacobs et al reported that transgene expression in the liver as the result of HTV injection equaled that of adenovirus injection.…”
mentioning
confidence: 99%